Comunicare le emozioni con la musica: contorni, forme vitali e qualità affettive - Meini, Cristina (Rivista Italiana di Filosofia del Linguaggio, 2020)
The nature of the relationship between music and emotions has always been disputed. In this paper, I shall endorse contour theory, which accounts for the expressiveness of music in terms of the perception of those resemblances that hold between its contour and the typical contour of human emotional expressions. My defense of contour theory will largely rely on the notion of vitality forms, the structures introduced by Daniel Stern in the context of infant research. I shall argue that, 1) although contours are displayed as vitality forms both in human behavior and in music, 2) in human behavior they are perceived as full-fledged emotional expressions, while 3) in music they are detected only through the two rough dimensions of valence and arousal.